Case report Acroangiodermatitis (Pseudo-Kaposi’s sarcoma); A challenging vascular condition - Jalal, Jalal Ali; Salih, Shanga Abdulkhaliq (Zanco Journal of Medical Sciences (ZJMS), 2014)
Acroangiodermatitis (synonym pseudo-Kaposi’s sarcoma) is an unusual, benign condition which clinically presents as erythematous, violaceous, brown, or purple-colored patches, plaques or nodules, mostly on the extensor surfaces of lower extremities. Acroangiodermatitis is often associated with different disorders including chronic venous insufficiency, arteriovenous malformations like Klippel-Trenauny syndrome, iatrogenic arteriovenous shunts like fistula in patients under hemolysis (lesions are developing distally to arteriovenous shunts), and in paralysed limbs. It has also been reported above amputation stump of the limbs (especially in those with poorly fitting suction-type devices). It resembles aggressive conditions like Kaposi’s sarcoma and requires histopathological examination for its diagnosis. We report a case of a 47-years old man with lesions of acroangiodermatitis in both lower legs and feet, secondary to chronic venous insufficiency. Histopathology showed dilated capillaries in the dermis with extravasated red blood cells, hemosiderin deposits and granulation tissue formation. In conclusion we would like to emphasize the importance of histopathology and immunohistochemistry in distinguishing this benign condition from similar looking malignant conditions especially Kaposi’s sarcoma.